A new immunoassay of hybrid nanomater conjugated to aptamers for the detection of dengue virus - Basso, Caroline R. [UNESP]; Crulhas, Bruno P. [UNESP]; Magro, Massimiliano; Vianello, Fabio; Pedrosa, Valber A. [UNESP] (Elsevier, 2019)
A new immunosensor using hybrid nanomaterials for the detection of dengue virus was demonstrated in this work. This immunosensor composed of nanoparticles of γ-Fe2O3(SAMN) modified with MPA- SAMN@MPA was characterized by FTIR spectroscopy, transmission electron microscopy,quartz crystal microbalance, UV–vis and LSPR technique. The binding of SAMN@MPA with AuNPs conjugated with aptamers(SAMN@MPA@AuNPs@aptamer) provides specific chemical bonds to four dengue serotypes. Colorimetric changes in the modification steps provided rapid visual detection of the virus without the use of equipment. Variations of aptamers concentrations 1.0-10.0 μM where the 3.0 μM aptamer concentration is sufficient to completely cover the surface of the modified AuNPs with an R2 value of> 0.99. This new proposed methodology presenting some advantages in relation to traditional detection methods such as time optimization and cost,can be used as a diagnostic method.
Keywords: Dengue virus; Hybrid nanomaterial; Localized surface plasmon resonance